Reductions in renin‐angiotensin system inhibitors following hospitalization for heart failure - Parag Goyal; Ligong Chen; Jennifer D. Lau; Robert S. Rosenson; Emily B. Levitan (ESC Heart Failure)
Abstract Aims Limited data are available that evaluate the efficacy of renin‐angiotensin system inhibitor (RASI) dose‐reduction in older adults with heart failure with reduced ejection fraction following a heart failure hospitalization. Methods and results We examined a 5% random sample of Medicare beneficiaries with prescription coverage who were discharged to home following a hospitalization for heart failure with reduced ejection fraction between 1 January 2007 and 30 June 2018 and were treated with RASI prior to hospitalization. We classified patients into three mutually exclusive groups based on RASI dosage before (prescription fills up to 90 days prior to) and after a hospitalization (prescription fills up to 365 days that were most proximate to the discharge date as possible)—same/increased dose, dose‐reduction, and discontinuation. We examined associations between RASI prescribing patterns and outcomes (mortality and all‐cause readmission at 30 days and 1 year) using Cox proportional hazards models. Among 12 794 unique older adults, 36.8% experienced a RASI reduction following their hospitalization for HFrEF—15.7% had a dose‐reduction and 21.1% had a discontinuation. Neither dose‐reduction nor discontinuation was associated with 30‐day mortality. Discontinuation was associated 1‐year mortality, 30‐day all‐cause readmission, and 1‐year all‐cause readmission, whereas dose‐reduction was not. Conclusion RASI dose‐reduction occurs in 1 out of 7 HF hospitalizations. In contrast to RASI discontinuation, RASI dose‐reduction was not associated with adverse short or long‐term outcomes. These findings indicate that RASI dose‐reduction is preferred over RASI discontinuation in selected situations where RASI reduction is needed.